2014
DOI: 10.11604/pamj.2014.18.279.1312
|View full text |Cite
|
Sign up to set email alerts
|

Association sarcoïdose et cirrhose biliaire primitive: à propos d’un nouveau cas

Abstract: La sarcoïdose est une maladie systémique d’étiologie inconnue. Elle est caractérisée par la présence de lésions granulomateuses, non caséeuses, au niveau des organes atteints. La cirrhose biliaire primitive (CBP) est une hépatopathie cholestatique auto-immune chronique, caractérisée par une destruction des canalicules biliaires et la présence d'anticorps antimitchondries type M2. L'association sarcoïdose et CBP est rare. Nous rapportons un nouveau cas de cette association avec revue de la littérature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…These are two hepatic granulomatoses whose differential diagnosis is sometimes very difficult to establish in practice. However, certain clinical, biological, immunological and histological parameters help to guide the clinician (Table 2) [1]. In our case, the diagnosis of primary biliary cirrhosis was revealed clinically by pruritus and biologically by a cholestasis syndrome.…”
Section: Clinical Casementioning
confidence: 71%
See 1 more Smart Citation
“…These are two hepatic granulomatoses whose differential diagnosis is sometimes very difficult to establish in practice. However, certain clinical, biological, immunological and histological parameters help to guide the clinician (Table 2) [1]. In our case, the diagnosis of primary biliary cirrhosis was revealed clinically by pruritus and biologically by a cholestasis syndrome.…”
Section: Clinical Casementioning
confidence: 71%
“…An etiological work-up was carried out, and serologies came back negative sarcoidosis and PBC and suggested that a common pathway contributes to granuloma formation in both conditions. One explanation for the apparent association between these conditions is that both share the same defect in cell-mediated immunity [1,11].…”
Section: Clinical Casementioning
confidence: 99%
“…Interstitial lung lesions and impaired respiratory function, particularly reduced CO diffusion, can also be observed in PBC [ 14 ]. However, certain clinical, biological, immunological, and histological parameters can assist the clinician [ 15 ].…”
Section: Discussionmentioning
confidence: 99%